Тайна речного тумана: роман / Алексей Мальцев - Мальцев Алексей Васильевич (Экcмо, 2019)
Экземпляры: (20220622) / Инвентарный номер: 35523 / Цена: / Сис.шифр: 84(2Роc=Рус)6 / Авт.знак: М 21 / ГРНТИ: 17.82.31 / ББК: 84(2Роc=Рус)6